Toward quantifying capacity losses due to solid electrolyte interphase evolution in silicon thin film batteries - Steinrück, Hans-Georg; Cao, Chuntian; Veith, Gabriel M.; Toney, Michael F. (The Journal of Chemical Physics)

Selbstbau eines digitalen Low-Cost-Fotometers für den Chemieunterricht - Witte, Thomas; Hanemann, Stefan; Sommerfeld, Herbert; Temmen, Katrin; Fechner, Sabine (CHEMKON)

Modeling and Simulation of an Industrial Formaldehyde Absorption System - Braz, Catarina G.; Lutters, Nicole; Rocha, Jorge; Alvim, Ricardo; Kenig, Eugeny; Matos, Henrique A. (Industrial & Engineering Chemistry Research)

Kinetics of Carbon Dioxide Removal Using N-Acetylglucosamine - Patil, Mayurkumar P.; Vaidya, Prakash D.; Kenig, Eugeny (ACS Omega)

Theoretical limits on the heat regeneration degree - Kronberg, Alexander; Glushenkov, Maxim; Knoke, Torben; Kenig, Eugeny (International Journal of Heat and Mass Transfer)

Numerical investigation of liquid flow morphology in structured packings - Olenberg, Alexander; Kenig, Eugeny (Chemical Engineering Science)

Numerical investigation of conjugate heat transfer in a pillow-plate heat exchanger - Zibart, A.; Kenig, E.Y. (International Journal of Heat and Mass Transfer)

Regeln der Kunst: Habitus, Literatur und ästhetische Form. - Eke, Norbert (Religiöse Erfahrung – Literarischer Habitus.)

Erstellung eines CFD-Modells für die Entwicklung eines innovativen Trennapparates zur Stickstoffrückgewinnung aus landwirtschaftlichen Abfällen - Bernemann, Sören Antonius
Keywords: CFD; landwirtschaftliche Abfälle; Volume-of-Fluid

Utopie als/der Störung. Heiner Müller und die „Lücke im Ablauf“. - Eke, Norbert (Rhetorik. Ein Internationales Jahrbuch)

Wider die Literaturwerkstättenliteratur? – Der Autor als „Obertonsänger“. Clemens J. Setz und die Gegenwartsliteratur. - Eke, Norbert („Es gibt Dinge, die es nicht gibt“. Vom Erzählen des Unwirklichen im Werk von Clemens J. Setz.)

Phase Transformation Characterization by Means of High Temperature Digital Image Correlation for Graded Thermo-Mechanical Processing of Sheet Parts - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (The Minerals, Metals & Materials Series)

„Das Schöne ist das Durchsichtige“. Norbert Otto Eke und Christof Hamann im Gespräch mit Herta Müller. In: Herta Müller. - Eke, Norbert (Text + Kritik 155/2020. 2. Auflage: Neufassung. Hg. von Norbert Otto Eke und Christof Hamann)

„Ein paar Freunde lachen. so verrückt daß ganz nahe / schon im Schach das Schweigen steht“. Lachen in Herta Müllers Texten. - Eke, Norbert (Herta Müller. Text + Kritik 155/2020. 2. Auflage: Neufassung. Hg. von Norbert Otto Eke und Christof Hamann.)

Auswahlbibliographie (Herta Müller) - Eke, Norbert (Herta Müller. Text + Kritik 155/2020. 2. Auflage: Neufassung. Hg. von Norbert Otto Eke und Christof Hamann.)

Popularisierung der Form. Volkstümlichkeit als Medium im Vormärz. In: Medien öffentlicher Rede nach Heine: zwischen Popularität und Populismus. Hg. von Dorothea Walzer. - Eke, Norbert (Beihefte zur Zeitschrift für deutsche Philologie)

Pilpul, oder: Er hatte geglaubt, es sei alles gut. Jüdische Mystik in Die Tochter. - Eke, Norbert (Im Kopf von Maxim Biller. Essays zum Werk.)

Vom ‚kleinen‘ ö und ‚großen‘ O. (Nicht allein) Komische Wendungen im Werk von Markus Orths. - Eke, Norbert (Von der ganz normalen Verrücktheit der Welt. Studien zum Werk von Markus Orths)

Der ‚Eigene Kalender‘ des Erinnerns: Die Wahrheit der erfundenen Erinnerung in Herta Müllers Romanen, Erzählungen und Essays - Eke, Norbert (German Life and Letters H. 1: Herta Müller and the Currents of European History)

Mark Hewitson: Militärwesen. Aus dem Englischen von Alena Diedrich und Norbert Otto Eke - Eke, Norbert (Vormärz-Hhandbuch.)

A Physics-Based Compact Static and Dynamic Characteristics Model for Al2O3/InxAl1−xN/AlN/GaN MOS-HEMTs - Beloufa, Abbes; Bouguenna, Driss; Kermas, Nawel; As, Donat Josef (Journal of Electronic Materials)

Photoluminescence Line‐Shape Analysis of Highly n‐Type Doped Zincblende GaN - Baron, Elias; Goldhahn, Rüdiger; Deppe, Michael; As, Donat Josef; Feneberg, Martin (physica status solidi (b))

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Herta Müller. Text + Kritik 155/2020. 2. Auflage: Neufassung. Hg. von Norbert Otto Eke und Christof Hamann. (edition text + kritik)

Materialabbau im Doppelschneckenextruder - Altepeter, Matthias; Schöppner, Volker (Kunststoffe)

Development of a Solids Conveying Throughput Model for Grooved Barrel Extruders based on Discrete Element Simulations - Schöppner, Volker; Brüning, Florian (Advances in Polymer Processing 2020: Proceedings of the International Symposium on Plastics Technology)
Regarding the design of single screw extruders, the prediction of the throughput needs to be of high accuracy. The calculation of the solids conveying throughput is particularly important for extruders with a grooved feed section. In contrast to smooth barrel extruders the throughput of the entire plant is determined at the feed section. Various simplifications are necessary for an analytical modelling of the solids conveying, e.g. the classification into conveying cases, the assumption of solid block flow and the assumption of pressure anisotropy coefficients. In numerical simulations with the Discrete Element Method (DEM), which has recently been successfully used to describe solids conveying in smooth barrel extruders, the simplifications mentioned above are not taken into account. Here, the pellets are approximated as spherical particles or particles composed of spheres. Based on virtual overlaps, contact models and the solution of Newton's equations of motion, a more complex consideration of the pellet flow is possible. In each iteration step of the simulation, the particle velocities, contact forces and derived quantities, e.g. the mass throughput in the screw channel and the grooves or the radial pressure build-up along the grooved barrel can be evaluated. Therefore, a DEM simulation model can be investigated by means of statistical design of experiments in order to convert the target values into a metamodel by regression. Long computation times of numerical simulations will be avoided in this matter as well as too simple assumptions of analytical approaches. The influencing parameters to be simulated are divided into material, geometry and process parameters. Relevant material parameters are the coefficients of friction of the polymer-polymer and polymer-steel surface as well as the restitution coefficient and the particle diameter. The geometry is varied in the form of the screw diameter, the channel depth and pitch, the number of grooves and their width, depth and angle. By varying the angle, both conventional axial grooves and helical grooves are taken into account. Finally, the process parameters speed and backpressure are also considered in the simulations. In order to reduce the simulation effort, irrelevant parameters are identified in preliminary investigations.

Einfluss der Materialschädigung auf die Schweißnahtqualität beim Warmgasstumpfschweißen von Polyamiden - Albrecht, Mirko; Bialaschik, Max; Gehde, Michael; Schöppner, Volker (DVS CONGRESS 2020 - Große Schweißtechnische Tagung)

Hot gas welding – Influences of the tool design - Albrecht, Mirko; Bialaschik, Max; Gehde, Michael; Schöppner, Volker

Structural optimization of a wheel force transducer component for more realistic acquisition of vehicle load data and fracture mechanical evaluation - Brüggemann, Jan-Peter; Risse, Lena; Woodcock, Steven Clifford; Joy, Tintu David; Neumann, Johannes; Vidner, Jakub; Kullmer, Gunter; Richard, Hans Albert (Applications in Engineering Science)

Vorhersage der Rissinitiierung in 3D-Strukturen mit ADAPCRACK3D - Joy, Tintu David; Kullmer, Gunter; Risse, Lena

Entwicklung einer Axialrissprobe zur Ermittlung von bruchmechanischen Kennwerten für Rohre - Kullmer, Gunter; Weiß, Deborah; Bauer, Benjamin; Richard, Hans Albert

Präoperative Studien zur Gestaltung von patientenspezifischen, medizinischen Hilfsmitteln - Risse, Lena

Plastisch- chirurgische Verfahren modifiziert nach Lexer zur Versorgung des Diabetischen Fußsyndroms in der Technischen Orthopädie – ein Standard im Hospital Geseke - Schraeder, Dirk Theodor; Geisen, Bärbel; Baumann, Dirk; Afaneh, Mamoun; Schafran, Tommy (Orthopädie Technik)

Joining of high-strength steel grades in lightweight structures using single-stage resistance element welding on conventional resistance spot welding machines - Günter, Heinrich; Meschut, Gerson (73rd IIW Annual Assembly and International Conference)

Value-centered design of a digital service robotics platform - Menzefricke, Jörn Steffen; Frank, Maximilian; Drewel, Marvin; Dumitrescu, Roman (Procedia CIRP)

Towards Meta-Algorithm Selection - Tornede, Alexander; Wever, Marcel Dominik; Hüllermeier, Eyke (Workshop MetaLearn 2020 @ NeurIPS 2020)

Identification of socio-technical changes caused by Industry 4.0 - Schnasse, Felix; Menzefricke, Jörn Steffen; Gabriel, Stefan; Hobscheidt, Daniela; Parlings, Matthias; Kühn, Arno; Dumitrescu, Roman (Proceedings of the Hamburg International Conference of Logistics (HICL))

Concept Development for a Functional Integrated Lightweight Battery Housing with Special Consideration of the Joining Technology - Krüger, Christopher; Schmolke, Tobias; Merdivan, David; Spohr, Sebastian; Urban, Peter; Meschut, Gerson

FOREL-Wegweiser: Handlungsempfehlungen für den ressourceneffizienten Leichtbau - Göddecke, Johannes; Meschut, Gerson; Gude, Maik; Lieberwirth, Holger; Tekkaya, Erman; Zaeh, Michael; Stegelmann, Michael; Müller, Michael; Böhme, Kurt; Krampitz, Thomas; Zöllner, Mareen; Hahn, Marlon; et al.

Experimentelle und numerische Untersuchung der Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson; Teutenberg, Dominik; Ummenhofer, Thomas; Albiez, Matthias; Damm, Jannis; Matzenmiller, Anton; Kötz, Fabian (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Entwicklung und Qualifizierung einer rechnergestützten Auswertemethode zur Differenzierung der Versagensanteile klebtechnisch gefügter Proben - Ditz, Michael; Meschut, Gerson; Schwarze, Thomas; Smart, Dominic

The Interdisciplinary Development of an Educational Game for Primary School Children--Lessons Learned - Winkelnkemper, Felix; Schulte, Carsten; Eilerts, Katja; Bechinie, Dominik; Huhmann, Tobias (EdMedia+ Innovate Learning)

Specification of Software Requirements for Condition Monitoring of Automation Systems - Pasic, Faruk; Wohlers, Benedict (2020 IEEE Tenth International Model-Driven Requirements Engineering (MoDRE))

Aligning Strategy and Structure for Smart Service Businesses in Manufacturing - Koldewey, Christian; Gausemeier, Jürgen; Chohan, Nadia; Frank, Maximilian; Reinhold, Jannik; Dumitrescu, Roman (Proceedings of the IEEE International Conference on Technology Management, Operations and Decisions ”Disruptive Technologies and Social Impacts”)

Systematische Entwicklung von Normstrategien für Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen; Bäsecke, Alexander; Reinhold, Jannik; Dumitrescu, Roman (ZWF Zeitschrift für wirtschaftliche Fabrikplanung)
Die Verfügbarkeit von Daten aus dem Betrieb hat durch die Einführung von vernetzten intelligenten Fertigungssystemen (cyber-physische Systeme) stark zugenommen. Hieraus eröffnen sich Erfolg versprechende Möglichkeiten für Smart Services und damit verbundene neue Geschäftsfelder. Voraussetzung für den Eintritt in ein neues Geschäft mit Smart Services ist eine fundierte Geschäftsstrategie. Wir zeigen die zentralen Gestaltungsfelder von Smart Service-Strategien auf und erläutern, wie sechs von uns ermittelte Normstrategien bei der Formulierung einer attraktiven Strategie helfen können.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Planning a Smart Service Business Integrating External Partners - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Managing Digital Open Innovation)
Today’s manufacturing industry is confronted with fundamental changes in value creation. The tension between the two megatrends of digitization and servitization leads to new hybrid market offerings, so-called smart services. Corresponding business models and value networks fundamentally differ from traditional ones. Developing smart services requires an advanced management of business models and new competences in young disciplines, while their provision requires new internal and external organizational structures or processes. To strengthen their competitive position, manufacturing companies need to extend their business model portfolios and adapt their value networks. However, the highly complex transformation of value creation especially challenges small and medium-sized companies due to limited competences and resources. They must consider opening their boundaries and collaborating with partners. In this chapter, we introduce a basic framework for designing smart services and present a methodology for the planning of a smart service business integrating external partners. The methodology is structured into five phases: Examination of smart service portfolio, analysis of business models and environment, business model portfolio planning, competence identification and analysis, and value creation planning. The methodology is explained by an example on cable marker printers.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Light diffraction in slab waveguide lenses simulated with the stepwise angular spectrum method - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optics Express)
A stepwise angular spectrum method (SASM) for curved interfaces is presented to calculate the wave propagation in planar lens-like integrated optical structures based on photonic slab waveguides. The method is derived and illustrated for an effective 2D setup first and then for 3D slab waveguide lenses. We employ slab waveguides of different thicknesses connected by curved surfaces to realize a lens-like structure. To simulate the wave propagation in 3D including reflection and scattering losses, the stepwise angular spectrum method is combined with full vectorial finite element computations for subproblems with lower complexity. Our SASM results show excellent agreement with rigorous numerical simulations of the full structures with a substantially lower computational effort and can be utilized for the simulation-based design and optimization of complex and large scale setups.
Keywords: tet_topic_waveguides

Lebensdauerberechnung hybrider Verbindungen - Çavdar, Serkan; Teutenberg, Dominik; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B.; Tittmann, K.; Koch, I.; Jäger, H.; Wacker, J.-D.; Rybar, G.; et al. (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Berechnen der Lebensdauer hybrider Verbindungen - Çavdar, Serkan; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B.; Tittmann, K.; Koch, I.; Jäger, H.; Wacker, J.-D.; Rybar, G.; Melz, T. (DVS Congress 2020)

Fatigue life prediction of adhesively bonded FRP-aluminium-joints with hyperelastic behavior under cyclic multiaxial stress state - Çavdar, Serkan; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B. (Joining in Car Body Engineering 2020)

Prozesskettenbegleitende Vorgehensweise beim Mechanischen Fügen - Heyser, Per; Scharr, Christian; Nehls, Thomas; Wiesenmayer, Sebastian; Flügge, Wilko; Meschut, Gerson (4. Workshop Digitalisierung)

Hamstrings substitution via anteromedial portal with optional anterolateral ligament reconstruction is the preferred surgical technique for anterior cruciate ligament reconstruction: a survey among ESSKA members. - Vascellari, A; Grassi, A; Canata, GL; Zaffagnini, S; Gokeler, A; Jones, H (Knee Surg Sports Traumatol Arthrosc)

Sagittal knee kinematics in relation with the posterior tibia slope during jump landing after an anterior cruciate ligament reconstruction. - Keizer, MNJ; Hijmans, JM; Gokeler, A; Otten, E; Brouwer, RW (J Exp Orthop)

Healthy subjects with lax knees use less knee flexion rather than muscle control to limit anterior tibia translation during landing. - Keizer, MNJ; Hijmans, JM; Gokeler, A; Benjaminse, A; Otten, E (J Exp Orthop)

Functional progression milestones following anterior cruciate ligament reconstruction are more appropriate than time-based criteria: a survey among the ESSKA. - Vascellari, A; Gokeler, A; Grassi, A; Canata, GL; Zaffagnini, S; Jones, H (Knee Surg Sports Traumatol Arthrosc)

Younger age and hamstring tendon graft are associated with higher IKDC 2000 and KOOS scores during the first year after ACL reconstruction. - Magnitskaya, N; Mouton, C; Gokeler, A; Nuehrenboerger, C; Pape, D; Seil, R (Knee Surg Sports Traumatol Arthrosc)

Passing return to sports tests after ACL reconstruction is associated with greater likelihood for return to sport but fail to identify second injury risk. - Welling, W; Benjaminse, A; Lemmink, K; Gokeler, A (Knee)

Towards Smart V2X-Connected Powertrains - Eisenbarth, Markus; Wegener, Marius; Scheer, René; Andert, Jakob; Buse, Dominik S.; Klingler, Florian; Sommer, Christoph; Dressler, Falko; Reinold, Peter; Gries, Rafael (IEEE Vehicular Technology Magazine (VTMag))

An Open Source Approach to Field Testing of WLAN up to IEEE 802.11ad at 60 GHz Using Commodity Hardware - Klingler, Florian; Hauptmeier, Fynn; Sommer, Christoph; Dressler, Falko (39th IEEE International Conference on Computer Communications (INFOCOM 2020), Poster Session)

Modern WLAN for V2X Applications: Exploiting Beamforming for Platooning - Hardes, Tobias; Klingler, Florian; Sommer, Christoph (12th IEEE Vehicular Networking Conference (VNC 2020))

Poster: Towards 2-Hop Neighbor Management for Heterogeneous Vehicular Networks - Turcanu, Ion; Kim, Minsuk; Klingler, Florian (12th IEEE Vehicular Networking Conference (VNC 2020))

Einfach den blauen Knopf drücken - Die Universität Paderborn entschied sich bereits Mitte März für Big Blue Button, ein offenes Videokonferenz-System, mit dem sich auch Lehr- und Lernprozesse unterstützen lassen - Oevel, Gudrun; Odenbach, Christopher (DUZ Wissenschaft & Management)

Method for data inventory and classification - Massmann, Melina; Meyer, Maurice; Frank, Maximilian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Data-Driven Product Generation and Retrofit Planning - Meyer, Maurice; Frank, Maximilian; Massmann, Melina; Wendt, Niklas; Dumitrescu, Roman (Procedia CIRP)

Datengetriebene Steigerung der Verfügbarkeit - Uhlmann, Eckart; Dumitrescu, Roman; Polte, Julian; Meyer, Maurice; Simsek, Deniz (wt Werkstattstechnik online)

Framework for Data Analytics in Data-Driven Product Planning - Massmann, Melina; Meyer, Maurice; Frank, Maximilian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia Manufacturing)

Combining Ideas and Artifacts: An Interaction-Focused View on Computing Education Using a Cybersecurity Example - Terfloth, Lutz; Budde, Lea; Schulte, Carsten
In this paper, we present a novel approach to design teaching interventions for computing education, elaborated using an example of cybersecurity education. Cybersecurity education, similar to other computing education domains, often focuses on one aspect and separate themselves from the other approach. In other words, they focus on one of the two different aspects: a) either teaching how to use and to behave, or b) how technology works. Here we suggest another point of focal awareness for teaching – interaction – that allows the recombination of both approaches in a novel way, leading to a reconstruction of the teaching and learning content in a way that – as we hope – supports an understanding on a higher level and thus gives the chance to better develop agency. For this didactic reconstruction of teaching content, we use an approach called the hybrid interaction system framework. In cybersecurity training, teaching interventions oftentimes are in a way successful but seem to not lead to long-lasting changes towards secure behavior. Using simply password security as an example, we show how this new approach recombines the two different priory mentioned teaching approaches in a novel way. Within this short paper, we present our current research progress, discuss potentials and values of the approach in general, and by way of example. Our intention of this submission and early disclosure is to spark discussion and generate further insights especially regarding the following question: What implications does the hybrid interaction system approach have on learning scenarios?

Balance task difficulty affects postural sway and cortical activity in healthy adolescents. - Gebel, A; Lehmann, T; Granacher, U (Exp Brain Res)

Platelet-rich plasma (PRP) as therapy for cartilage, tendon and muscle damage - German working group position statement. - Tischer, T; Bode, G; Buhs, M; Marquass, B; Nehrer, S; Vogt, S; Zinser, W; Angele, P; Spahn, G; Welsch, GH; Niemeyer, P; Madry, H (J Exp Orthop)

The influence of motor tasks and cut-off parameter selection on artifact subspace reconstruction in EEG recordings - Anders, P; Müller, H; Skjæret-Maroni, N; Vereijken, B; Baumeister, Jochen (Medical & Biological Engineering & Computing)

A self stabilizing protocol for well-formed trees in hybrid networks - Jochmaring, Moritz

Impact of Chlorine on the Internal Transition Rates and Excited States of the Thermally Delayed Activated Fluorescence Molecule 3CzClIPN - Streiter, Martin; Fischer, Tillmann G.; Wiebeler, Christian; Reichert, Sebastian; Langenickel, Jörn; Zeitler, Kirsten; Deibel, Carsten (The Journal of Physical Chemistry C)
Keywords: pc2-ressources

A photoredox catalysed Heck reaction via hole transfer from a Ru(II)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg K N; Gerstmann, Uwe; Meier, Armin; Schmidt, W Gero; Wilhelm, René (Royal Society of Chemistry)

A systematic literature review of model-driven security engineering for cyber–physical systems - Geismann, Johannes; Bodden, Eric (Journal of Systems and Software)

Explaining Static Analysis with Rule Graphs - Nguyen Quang Do, Lisa; Bodden, Eric (IEEE Transactions on Software Engineering)

PASAPTO: Policy-aware Security and Performance Trade-off Analysis - Computation on Encrypted Data with Restricted Leakage - Fischer, Andreas; Janneck, Jonas; Kussmaul, Jörn; Krätzschmar, Nikolas; Kerschbaum, Florian; Bodden, Eric (2020 IEEE Computer Security Foundations Symposium (CSF))

Heaps'n Leaks: How Heap Snapshots Improve Android Taint Analysis - Benz, Manuel; Krogh Kristensen, Erik; Luo, Linghui; P. Borges Jr., Nataniel; Bodden, Eric; Zeller, Andreas (International Conference for Software Engineering (ICSE))

Computation on Encrypted Data using Dataflow Authentication - Fischer, Andreas; Fuhry, Benny; Kerschbaum, Florian; Bodden, Eric (Privacy Enhancing Technologies Symposium (PETS/PoPETS))

CogniCrypt_GEN - Generating Code for the Secure Usage of Crypto APIs - Krüger, Stefan; Ali, Karim; Bodden, Eric (International Symposium on Code Generation and Optimization (CGO))

CogniCrypt -- The Secure Integration of Cryptographic Software - Krüger, Stefan
Frühere Studien haben empirisch offenbart, dass Fehlbenutzungen von kryptographischen APIs in Softwareanwendungen weitverbreitet sind. Dies geschieht vor allem, weil Software-Entwickler_innen aufgrund schlechten API-Designs und fehlenden Kryptographiewissens Probleme bekommen, wenn sie versuchen kryptographische Features zu implementieren. Die Literatur liefert mehrere Ansätze und Vorschläge diese Probleme zu lösen, aber alle scheitern schlussendlich auf die eine oder andere Weise daran die Anforderungen der Entwickler_innenzu erfüllen. Das Resultat ist eine insgesamt lückenhafte Landschaft verschiedener nur wenigkomplementärer Ansätze.In dieser Arbeit adressieren wir das Problem kryptographischer Fehlbenutzungen systematischer durch CogniCrypt. CogniCrypt integriert verschiedene Arten von Tool Supportin einen gemeinsamen Ansatz, der Entwickler_innen davon befreit wissen zu müssen, wie diese APIs benutzt werden müssen. Zentral für unseren Ansatz ist CrySL, eine Beschreibungssprache,die die kognitive Lücke zwischen Kryptographie-Expert_innen und Software-Entwickler_innenüberbrückt. CrySL ermöglicht es Kryptographie-Expert_innen zu spezifizeren, wie die APIs,die sie bereitstellen, richtig benutzt werden. Wir haben einen Compiler für CrySL implementiert, der es erlaubt auf CrySL-Spezifikationen aufbauenden Tool Support zu entwickeln. Wir haben weiterhin die statische Analyse CogniCrypt_SAST und den Code-Generator CogniCrypt_GEN entwickelt. Schlussendlich haben wir CogniCrypt prototypisch implementiert und diesen Prototyp in einem kontrollierten Experiment evaluiert.

Model-driven engineering and usability evaluation of self-adaptive user interfaces - Yigitbas, Enes (ACM SIGWEB Newsletter)

Cutting through the Jungle: Disambiguating Model-based Traceability Terminology - Holtmann, Jörg; Steghofer, Jan-Philipp; Rath, Michael; Schmelter, David (2020 IEEE 28th International Requirements Engineering Conference (RE))
Traceability, a classic requirements engineering topic, is increasingly used in the context of model-based engineering. However, researchers and practitioners lack a concise terminology to discuss aspects of requirements traceability in situations in which engineers heavily rely on models and model-based engineering. While others have previously surveyed the domain, no one has so far provided a clear, unambiguous set of terms that can be used to discuss traceability in such a context. We therefore set out to cut a path through the jungle of terminology for model-based traceability, ground it in established terminology from requirements engineering, and derive an unambiguous set of relevant terms. We also map the terminology used in existing primary and secondary studies to our taxonomy to show differences and commonalities. The contribution of this paper is thus a terminology for model-based traceability that allows requirements engineers and engineers working with models to unambiguously discuss their joint traceability efforts.

Scenario-based Specification of Security Protocols and Transformation to Security Model Checkers - Koch, Thorsten; Dziwok, Stefan; Holtmann, Jörg; Bodden, Eric (ACM/IEEE 23rd International Conference on Model Driven Engineering Languages and Systems (MODELS ’20))

Model-Driven Information Flow Security Engineering for Cyber-Physical Systems - Gerking, Christopher

Simulationsbasierte Betriebsfestigkeitsanalyse stanzgenieteter Bauteile - Otroshi, Mortaza; Meschut, Gerson; Masendorf, Lukas; Esderts, Alfons

GEMINI-Modellierungssprache für Wertschöpfungssysteme - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

GEMINI-Geschäftsmodellmuster-Kartenset - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodellvalidierung - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodell-Roadmapping - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Nanoantennas embedded in zinc oxide for second harmonic generation enhancement - Volmert, Ruth; Weber, Nils; Meier, Cedrik (Journal of Applied Physics)
Plasmonic nanoantennas for visible and infrared radiation strongly improve the interaction of light with the matter on the nanoscale due to their strong near-field enhancement. In this study, we investigate a double-resonant plasmonic nanoantenna, which makes use of plasmonic field enhancement, enhanced outcoupling of second harmonic light, and resonant lattice effects. Using this design, we demonstrate how the efficiency of second harmonic generation can be increased significantly by fully embedding the nanoantennas into nonlinear dielectric material ZnO, instead of placing them on the surface. Investigating two different processes, we found that the best fabrication route is embedding the gold nanoantennas in ZnO using an MBE overgrowth process where a thin ZnO layer was deposited on nanoantennas fabricated on a ZnO substrate. In addition, second harmonic generation measurements show that the embedding leads to an enhancement compared to the emission of nanoantennas placed on the ZnO substrate surface. These promising results facilitate further research to determine the influence of the periodicity of the nanoantenna arrangement of the resulting SHG signal.

Offenzeit plasmaaktivierter Polymeroberflächen für robuste klebtechnische Prozesse – OffPlas - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson; Stepanov, Sergey; Stalling, Annika; Ihde, Jörg; Mayer, Bernd (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Analyse und Vorhersage rezeptur- und zeitabhängiger Enthaftungserscheinungen geklebter SMC-Bauteile - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Lokales Konzept zur Auslegung von elastischen Klebverbindungen (LoKAl) - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson; Philipp, Jens; Stammen, Elisabeth; Dilger, Klaus (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Aktivieren für robuste Klebprozesse - Wie lange sind plasmaaktivierte Polymeroberflächen offen? - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson; Stepanov, Sergey; Ihde, Jörg; Mayer, Bernd (Plastverarbeiter)

Offenzeit plasmaaktivierter Polymeroberflächen für robuste klebtechnische Prozesse - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson; Stepanov, Sergey; Ihde, Jörg; Mayer, Bernd

Analyse rezepturabhängiger und alterungsbedingter Enthaftungserscheinungen geklebter SMC-Bauteile - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson

Jointly Optimal Dereverberation and Beamforming - Boeddeker, Christoph; Nakatani, Tomohiro; Kinoshita, Keisuke; Haeb-Umbach, Reinhold (ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Towards a speaker diarization system for the CHiME 2020 dinner party transcription - Boeddeker, Christoph; Cord-Landwehr, Tobias; Heitkaemper, Jens; Zorila, Catalin; Hayakawa, Daichi; Li, Mohan; Liu, Min; Doddipatla, Rama; Haeb-Umbach, Reinhold (Proc. CHiME 2020 Workshop on Speech Processing in Everyday Environments)

Asteroid: The PyTorch-Based Audio Source Separation Toolkit for Researchers - Pariente, Manuel; Cornell, Samuele; Cosentino, Joris; Sivasankaran, Sunit; Tzinis, Efthymios; Heitkaemper, Jens; Olvera, Michel; Stöter, Fabian-Robert; Hu, Mathieu; Martín-Doñas, Juan M.; Ditter, David; Frank, Ariel; et al. (Interspeech 2020)
This paper describes Asteroid , the PyTorch -based audio source separation toolkit for researchers. Inspired by the most successful neural source separation systems, it provides all neural building blocks required to build such a system. To improve reproducibility, Kaldi-style recipes on common audio source separation datasets are also provided. This paper describes the software architecture of Asteroid and its most important features. By showing experimental results obtained with Asteroid ’s recipes, we show that our implementations are at least on par with most results reported in reference papers. The toolkit is publicly available at github.com/mpariente/asteroid.

Orientierungen in der digitalen Welt